Student pharmacists' and recent graduates' perception of and interest in independent pharmacy ownership - Ashley M. Sweaney; Kristin A Casper; Cara D. Hoyt; Allison M. Wehr (University of Minnesota Libraries Publishing, 2014)
Objectives: To assess student pharmacists' and recent graduates' interest in independent community pharmacy ownership and compare perceptions of pharmacy ownership among students and recent graduates. Methods: An anonymous online survey was administered to student pharmacists currently licensed as interns and pharmacists licensed by examination from January 2010 to October 2012 within the state of Ohio. Results: 355 surveys were completed during the study period, with 200 (56.3%) completed by student pharmacists. Student pharmacists were significantly more interested in pharmacy ownership (p < 0.001) and had significantly higher self-reported likelihood of ownership (p = 0.03) compared to recent graduates. Top ranked advantages to ownership for both groups included professional autonomy, development of innovative services, and amount of time spent in patient care activities. The majority of respondents had been exposed to pharmacy ownership within a course, student organization, or experiential rotation, but felt they needed more training in financial, legal, and regulatory issues. Conclusion: Many student pharmacists and recent graduates are interested in pharmacy ownership. However, the majority of respondents feel it is unlikely they will own a pharmacy in the future. Resources need to be expanded for those interested in this career path.   Type: Original Research